Case Report: Rare Iliac Vein Compression (May-Thurner) Syndrome in a Pediatric Patient - Lianfu Ji; Fan Yang; Xuan Chen; Jinlong Chen; Xueying Cheng; Jie Yin; Yuming Qin; Shiwei Yang (Frontiers Media S.A., 2021)
Iliac vein compression syndrome (IVCS) or May-Thurner syndrome occurs predominantly in young to middle-aged women. Here we reported a case of IVCS in a 5-year-old boy. The child was admitted to our vasculocardiology department with left lower extremity that had been swollen for 1 month. Blood tests revealed coagulation routine and platelets in the normal ranges. Computer tomography angiography (CTA) and magnetic resonance imaging (MRI) showed the left common iliac vein had become narrow before it entered the right common iliac vein. To further clarify, we performed angiography, which clearly showed the stenosis and the blood return of the left common iliac vein. So IVCS was diagnosed. What is more, we found the aorta descended to the right of the spine, and this may be the reason for the apparent compression of the left common iliac vein. Given the young age and mild symptoms of the child, the treatment was conservative mainly including elevation of the affected limb, wearing medical elastic socks, and short-term oral aspirin for anticoagulation. Meanwhile, the boy is being followed up closely. If the swelling of the left lower extremity significantly increases, stent placement may need to be considered in the future.